Can professors be socialized in good teaching practices? The case of the Project Visibilidad - López María Muradás; Mendoza, Pilar (Education Policy Analysis Archives, 2010)
The purpose of this study is to analyze the socialization to teaching experience of faculty who participated in the project Visibilidad. The main objective of this project was to obtain knowledge related to teaching from faculty who are considered good teachers in Spanish universities. This knowledge could enlighten how the socialization to teaching occurs as well as insights on how to improve the process. Based on the international literature on socialization to teaching in higher education and using a methodology of generating themes inductively, the experiences of faculty at the beginning of their careers were analyzed. The data was collected using semi-structured interviews. We found that role models of socialization, self-reflection and formal socialization are the most common experiences reported by participants. This suggests that reinforcing these elements deliberately at an institutional level, it is possible to improve the socialization process of new faculty in higher education as well as their teaching practices.